THE INFLUENCE OF VALUE SOCIALIZATION METHOD ON INDEPENDENT CHARACTERS AND RESPONSIBILITIES IN EARLY CHILDREN IN THE KINDERGARTEN XAVERIUS 1 CITY OF JAMBI - Pangaribuan, Tumewa; Yusra, Affan (Indonesian Journal of Early Childhood Education Studies, 2019)
This study aims to: 1) Describe the use of the value socialization method to the independent characteristics and responsibilities of Xaverius 1 Kindergarten 1 Jambi City children. 2) Describe the difference between the control class without using the method with the experimental class using the value socialization method on the independence and responsibility of children in Kindergarten Xaverius 1 Jambi City. While the tool used in research is the scale of child development achievements. This type of research used in this study was to use a quasi-experimental design with a Randomized Pretest-Posttest Control Group design with a level of 0.05%. The results showed 0.170 smaller than <0.05, it can be concluded that Ha was accepted